Self Assembly and Properties of C:WO3 Nano-Platelets and C:VO2/V2O5 Triangular Capsules Produced by Laser Solution Photolysis - Sideras-Haddad E (Nanoscale Research Letters, 2009)
Abstract Laser photolysis of WCl6 in ethanol and a specific mixture of V2O5 and VCl3 in ethanol lead to carbon modified vanadium and tungsten oxides with interesting properties. The presence of graphene’s aromatic rings (from the vibrational frequency of 1,600 cm−1) together with C–C bonding of carbon (from the Raman shift of 1,124 cm−1) present unique optical, vibrational, electronic and structural properties of the intended tungsten trioxide and vanadium dioxide materials. The morphology of these samples shows nano-platelets in WO x samples and, in VO x samples, encapsulated spherical quantum dots in conjunction with fullerenes of VO x . Conductivity studies revealed that the VO2/V2O5 nanostructures are more sensitive to Cl than to the presence of ethanol, whereas the C:WO3 nano-platelets are more sensitive to ethanol than atomic C.